Revising chronological uncertainties in marine archives using global anthropogenic signals: a case study on the oceanic ¹³C Suess effect - Irvalı, N; Ninnemann, US; Olsen, A; Rose, NL; Thornalley, DJR; Mjell, TL; Counillon, F (Copernicus GmbH, 2024)
Marine sediments are excellent archives for reconstructing past changes in climate and ocean circulation. Overlapping with instrumental records, they hold the potential to elucidate natural variability and contextualize current changes. Yet, dating uncertainties of traditional approaches (e.g., up to ± 30–50 years for the last 2 centuries) pose major challenges for integrating the shorter instrumental records with these extended marine archives. Hence, robust sediment chronologies are crucial, and most existing age model constraints do not provide sufficient age control, particularly for the 20th century, which is the most critical period for comparing proxy records to historical changes. Here we propose a novel chronostratigraphic approach that uses anthropogenic signals such as the oceanic 13C Suess effect and spheroidal carbonaceous fly-ash particles to reduce age model uncertainties in high-resolution marine archives. As a test, we apply this new approach to a marine sediment core located at the Gardar Drift, in the subpolar North Atlantic, and revise the previously published age model for this site. We further provide a refined estimate of regional reservoir corrections and uncertainties for Gardar Drift.